Influence of Chemical Blends on Palm Oil Methyl Esters’ Cold Flow Properties and Fuel Characteristics - Obed M., Ali; Talal, Yusaf; R., Mamat; Nik Rosli, Abdullah; Abdul Adam, Abdullah (MDPI AG, 2014)
Alternative fuels, like biodiesel, are being utilized as a renewable energy source and an effective substitute for the continuously depleting supply of mineral diesel as they have similar combustion characteristics. However, the use of pure biodiesel as a fuel for diesel engines is currently limited due to problems relating to fuel properties and its relatively poor cold flow characteristics. Therefore, the most acceptable option for improving the properties of biodiesel is the use of a fuel additive. In the present study, the properties of palm oil methyl esters with increasing additive content were investigated after addition of ethanol, butanol and diethyl ether. The results revealed varying improvement in acid value, density, viscosity, pour point and cloud point, accompanied by a slight decrease in energy content with an increasing additive ratio. The viscosity reductions at 5% additive were 12%, 7%, 16.5% for ethanol, butanol and diethyl ether, respectively, and the maximum reduction in pour point was 5 °C at 5% diethyl ether blend. Engine test results revealed a noticeable improvement in engine brake power and specific fuel consumption compared to palm oil biodiesel and the best performance was obtained with diethyl ether. All the biodiesel-additive blend samples meet the requirements of ASTM D6751 biodiesel fuel standards for the measured properties.